Questions in secondary classrooms: Toward a theory of questioning. (March 2022) - Alexander, Kimberly; Gonzalez, Charles H.; Vermette, Paul J.; Di Marco, Sabrina
At the heart of the teaching practice is the art of questioning. Costa and Kallick noted that questions are the means by which insights unlock thinking. Effective questioning is essential to effective teaching. Despite this, a cohesive theory on the method of questioning has yet to be developed. A discussion of questioning is vital to moving the teaching profession forward. In this article, we propose a model of effective questioning that we see as the first step toward identifying a unifying theory of questioning. Our model contains the following three components: (1) a well-structured item (a good question), (2) clear expectations for the response (which we call 'the five considerations'), and (3) a constructivist conversation. This work succeeds in bridging the gap between practice and theory that may otherwise limit good teachers from utilizing their questions in the most effective manner. Because of this, our model should be of use to teachers, teacher educators, professional developers, educational researchers, and theoreticians. We hope that a continued discussion of questioning ensues in all of these circles, so that our field can move closer toward the development of a theory of questioning.